Characterization of the waste generated by the canteen of the Universidad Nacional Santiago Antúnez de Mayolo - Cruz Nieto, Dante Daniel (2020)
The research tackles the characterization of the solid waste generated by the canteen of the Universidad Nacional Santiago Antúnez de Mayolo, which aims to determine the amount and propose its final disposal. For this, it was quantified by days, months and its management was proposed; obtained the data were operated with the basic statistics and the bar graphs were prepared for analysis and interpretation. The results determined that the greatest quantity was obtained on Thursdays and Fridays with 17.7 kg and 18.5 kg respectively, in the quantity per month it was November and December with 402.22 kg and 442.38 kg; As a percentage of the characteristics of the waste, the organic waste obtained 66.80%, inorganic waste 24.65% and inert waste 8.55%. Regarding the proposal for organic waste, 41% is proposed for animal feed, as fertilizer for orchards 32% and green areas 20%. Regarding inorganic waste, it is thrown away by 39%, sells 31% and as added value 18%. The results of the characterization and proposal of solid waste make it possible to know the availability for final disposal in its use, giving it an added value, which will favor as a sustainable resource and reduce environmental pollution.